Lower–Middle Ordovician carbon and oxygen isotope chemostratigraphy at Hällekis, Sweden: implications for regional to global correlation and palaeoenvironmental development. (3rd October 2018) - Lindskog, Anders; Eriksson, Mats E.; Bergström, Stig M.; Young, Seth A.
Abstract : A high‐resolution chemostratigraphical (coupled δ 13 Ccarb and δ 18 Ocarb ) study of the topmost Floian through the middle Darriwilian (Ordovician) succession at the Hällekis quarry, Kinnekulle, southern Sweden, shows relatively steady isotopic values with overall minor changes, although some notable short‐ and long‐term shifts are discernible. A pronounced positive shift in δ 13 C in the uppermost part of the study succession is identified as the Middle Darriwilian Isotopic Carbon Excursion (MDICE), representing the only named global isotopic excursion in the data set. Regional and global comparisons suggest that few details in the different carbon and oxygen isotope curves can be confidently correlated, but longer‐term patterns appear quite consistent. Trends in the isotope data are in agreement with palaeogeographical reconstructions. Differences in stratigraphical patterns of both carbon and oxygen isotopes between localities suggest strong secular development at several spatiotemporal scales; any global signal involving relatively minor isotopic shifts is often masked/subdued by local and regional overprinting and care should be taken not to overinterpret data sets. Collectively, the data suggest rising sea levels and cooling climates through the studied time interval, but detailed interpretations remain problematic.